If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9r + -1 = 53 Reorder the terms: -1 + 9r = 53 Solving -1 + 9r = 53 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 9r = 53 + 1 Combine like terms: -1 + 1 = 0 0 + 9r = 53 + 1 9r = 53 + 1 Combine like terms: 53 + 1 = 54 9r = 54 Divide each side by '9'. r = 6 Simplifying r = 6
| -6x-y=-4 | | 82+y=15 | | x+(-3/2)=-5 | | 8p-p+3=10p-6 | | 3(y-5)=21 | | 4x-3(-3x-26)=208 | | 76=-5x+3(-3x+2) | | 7a-5=4a+7 | | 22m=374 | | (5a-2)(a+4)= | | -06+0.05f=5.3 | | 14=.25w-8 | | 3x=165 | | x+70=50 | | (4u^3+4u^2+2)+(6u^3-2u+8)=0 | | 0.3x+.1X=3.9 | | (5c-4)(c+6)= | | 0.7/20=n/100 | | 8-t/2=54 | | 5w=-1/3 | | 4t^2-25t+25=0 | | x+(x-5)+(x+20)=180 | | 2r^2-12r-146=-2 | | 14=.25(w-8) | | (-3x^2-7x+9)+(-5x^2+6x-4)=y | | -3x/4 | | 9x^9-72x^2= | | x^2=72+x | | 20(x)(x)(x)=1.99 | | 5z^2+10z-az-2a= | | (2/9)(-7) | | 2/5x+3 |